THE ROLE OF INTERACTIVE METHODS IN FORMING STUDENTS' SPEECH IN MOTHER LANGUAGE LESSONS - Тажиева Зуҳра Камалбаевна (Journals Park Publishing, 2024)
Improving the effectiveness of mother tongue classes requires equipping the educational process with new pedagogical technologies, technical and informational tools at the level of current demand. This article discusses "Interactive" methods and modern educational technologies, which are considered to be the most modern and effective methods of teaching in the educational process (mother tongue lessons).
Keywords: education, pedagogy, method, teaching method, technology, interactive, problem, modular, test lesson, audiovisual, informational means.